TINJAUAN HUKUM PERJANJIAN JUAL BELI OBAT TRADISIONAL TANPA IZIN EDAR: (Studi Kasus Obat Tradisional Montalin) - Muhammad Irsyadhul Ula; Ainun Garini Paramita (JOURNAL SAINS STUDENT RESEARCH, 2023)
The sale of traditional medicines that do not have a distribution permit is still widespread in Indonesia, the Food and Drug Supervisory Agency (BPOM) continues to strive to eradicate the distribution of traditional medicines that do not have a distribution permit, the sale of these traditional drugs also violates the 4 legal conditions of the agreement, namely condition number 4 (four) where an agreement must fulfill halal reasons, traditional medicines that do not have a distribution permit do not have halal status and a distribution permit certificate, this can harm consumers who consume these traditional medicines.